2013
DOI: 10.1007/s12024-013-9459-x
|View full text |Cite
|
Sign up to set email alerts
|

Edema is a sign of early acute myocardial infarction on post-mortem magnetic resonance imaging

Abstract: The aim of this study was to investigate if acute myocardial infarction can be detected by post-mortem cardiac magnetic resonance (PMMR) at an earlier stage than by traditional autopsy, i.e., within less than 4 h after onset of ischemia; and if so, to determine the characteristics of PMMR findings in early acute infarcts. Twenty-one ex vivo porcine hearts with acute myocardial infarction underwent T2-weighted cardiac PMMR imaging within 3 h of onset of iatrogenic ischemia. PMMR imaging findings were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The literature provides strong evidence that T 2 weighted MR images are of paramount importance in post-mortem imaging: their ability to highlight fluid accumulations makes them an ideal diagnostic tool for a wide range of pathologies, including subcutaneous haematoma, bone contusion, organ laceration, internal haemorrhage and fluid collections, ischaemic injury of the heart, brain oedema, pericardial or pleural effusion and pulmonary oedema. 6,19,23,31,[39][40][41][42][43][44] In our experience, STIR sequences are most suitable for screening purposes because they emphasize the signal from tissues with long T 2 relaxation times 45 and fluid accumulations literally flash like light bulbs when scrolling through images on STIR sequences. Thus, we refer to this phenomenon as the "forensic sentinel sign" ( Figure 6).…”
Section: Step 2: Basic Application Of Forensic Pmmrmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature provides strong evidence that T 2 weighted MR images are of paramount importance in post-mortem imaging: their ability to highlight fluid accumulations makes them an ideal diagnostic tool for a wide range of pathologies, including subcutaneous haematoma, bone contusion, organ laceration, internal haemorrhage and fluid collections, ischaemic injury of the heart, brain oedema, pericardial or pleural effusion and pulmonary oedema. 6,19,23,31,[39][40][41][42][43][44] In our experience, STIR sequences are most suitable for screening purposes because they emphasize the signal from tissues with long T 2 relaxation times 45 and fluid accumulations literally flash like light bulbs when scrolling through images on STIR sequences. Thus, we refer to this phenomenon as the "forensic sentinel sign" ( Figure 6).…”
Section: Step 2: Basic Application Of Forensic Pmmrmentioning
confidence: 99%
“…The extent of ischaemia-induced oedema depends heavily on the occurrence of vascular reperfusion. 42,65 Combined ischaemia/reperfusion injury results in more extensive oedema (with both intracellular and interstitial fluid accumulation) than ischaemic injury without vascular reperfusion (where fluid accumulation is often limited to the intracellular space). 65 A recent study by Ruder et al 42 revealed that oedema from ischaemia/ reperfusion injury can be detected on PMMR within 3 h after the onset of vascular occlusion.…”
Section: Cardiovascular Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Jackowski et al [57][58][59][60] demonstrated that PMMR enables the detection of myocardial infarction in situ and the estimation of infarct age based on signal behaviour and quantitative T1, T2 and proton density values, better if temperature-corrected ( Figure 2). Oedema was suggested as a sign of early myocardial infarction in ex vivo porcine hearts [61]. In 2018, Wagensveld et al [62] found that the combination of MRI with heart biopsies had high sensitivity and specificity for the detection of acute and chronic myocardial infarction at postmortem examination.…”
Section: Valves and Wall Thicknessmentioning
confidence: 99%
“…Early work was not autopsy controlled, 75 while later articles were less optimistic, 4 but, more recently, changes on T 2 weighted images have been shown in animal models and clinical studies. [76][77][78] Clinical MRI scanning tells us that there may be more complex contrast enhancement changes that may be seen, such as the delayed myocardial enhancement occurring in regions of myocardial infarction. 79 Whole body contrast angiography is possible, 80 and there is no reason that targeted techniques cannot be translated to MRI, except for cost and time.…”
Section: Traumatic Death and Identificationmentioning
confidence: 99%